MNGI-03. ESTROGEN HORMONE REPLACEMENT THERAPY IN INCIDENTAL MENINGIOMA - A GROWTH RATE ANALYSIS. (11th November 2019) - Kamson, David; Yuen, Carlen; Castillo Saavedra, Laura; Jenkins Vogel, Tilley; Merrell, Ryan; Walker, Matthew
Abstract: BACKGROUND: Meningiomas are common intracranial neoplasms with female predominance and sharply rising incidence in the perimenopausal years. As they often express estrogen receptors, hormone replacement therapy (HRT) poses a theoretical risk inducing accelerated growth. Although HRT has been linked to slightly increased incidence, its actual effect on meningioma growth-rate had not been studied in a clinical population. AIM: We aimed to retrospectively compare tumor characteristics and grow-rates of incidental meningiomas of those with a ≥6-month history of estrogen-based HRT (e-HRT) before or during surveillance compared to those without (no-HRT). METHODS: Forty females with e-HRT and 80 age-matched HRT-naïve females were identified from the NorthShore Incidental Meningioma Database. Tumor characteristics and diameters were analyzed on initial and all follow-up MRIs. Progression-free survival (PFS) was assessed. RESULTS: Twenty-one patients completed e-HRT before, 10 started before and continued during, and 9 started e-HRT during surveillance. Patient and radiographic characteristics were similar between the groups (mean age 62y in both, parity; tumor calcification, T2W-intensity), whereas those with e-HRT had significantly lower body weight (68±16kg vs. 77±21kg; p=0.01) and tended to have longer follow-up (6.7±3.9yrs vs. 5.3±3.9yrs; p=0.07). Those with e-HRT had significantly smaller meningiomas (13±6mm vs. 16±9mm at diagnosis and 15±7mm vs. 19±11mm at end of follow-up; p=0.03 for both), and slower absolute grow-rates (0.5±0.8 vs 1.0±2.1mm/year; p=0.05) than those of no-HRT. Proportional growth-rate differences were not significant (3.3%/year vs. 5.4%/year p >0.05). Subgroup analyses showed no difference between vaginal vs. oral/subcutaneous/transdermal route e-HRT vs. no-HRT. PFS defined by RECIST1.1, RANO and clinical (new symptoms or treatment) criteria were 11.1, 6.6 and 14.7years in e-HRT versus 10.5, 5.4 and 11.4years in no-HRT. None of the differences were significant (log-rank p >0.1). CONCLUSIONS: In this preliminary analysis, those with e-HRT had smaller tumors that grew slower, suggesting that e-HRT may be safe in incidental meningioma.